Study of application of industrial design in the manufacturing sector in the industrial corridor of Boyacá - Ramirez Leon, Cecilia (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This article is the result of a qualitative research done between 2008 and 2010 whose goals are knowing the perceptions of Boyacá companies to the Industrial Design.  The object of the study is conformed by companies from Tunja, Duitama and Sogamoso with their areas of  influence. The study found that there is not a clear idea in Industrial sector in Boyacá of the existence of the Industrial design as a profession.  No one has a notion about its role or its strategic value, neither related to productivity nor to business competitiveness. This finding is a diagnostic tool as well as an analysis tool for establishing the impact of the discipline in the business sector in the region.